2011
DOI: 10.3892/or.2010.1103
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic significance of lost or decreased PDCD5 expression in human epithelial ovarian carcinomas

Abstract: Abstract. Programmed cell death 5 (PDCD5) is a novel apoptosis-promoting protein. Although the decreased expression of PDCD5 has been recently found in a few types of human tumors, the status and significance of PDCD5 in ovarian cancer has not been evaluated. In the present study, we detected PDCD5 expression in 20 normal human ovaries and 26 serous cystadenomas and 41 serous cystadenocarcinomas by RT-PCR, Western blotting and immunohistochemistry, and analyzed the relationship between PDCD5 expression and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 14 publications
(21 reference statements)
1
36
1
Order By: Relevance
“…PDCD1, often known as PD-1, is the member that has been most extensively studied and shown to negatively regulate T cell responses, in collaboration with its two ligands, PD-L1 and PD-L2 (51)(52)(53). In addition to PDCD5, other programmed cell death proteins are also known to play important roles in apoptosis and/or cell cycle progression (54)(55)(56)(57), and are also dysregulated in many types of human cancers (13,16,(58)(59)(60)(61)(62)(63). Opposite to what we observed for PDCD5, depletion of PDCD2 in human acute leukemia cells impairs their proliferation, induces cell cycle arrest and p53 activation while overexpression of PDCD2 facilitates cell growth in cancers (55,64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDCD1, often known as PD-1, is the member that has been most extensively studied and shown to negatively regulate T cell responses, in collaboration with its two ligands, PD-L1 and PD-L2 (51)(52)(53). In addition to PDCD5, other programmed cell death proteins are also known to play important roles in apoptosis and/or cell cycle progression (54)(55)(56)(57), and are also dysregulated in many types of human cancers (13,16,(58)(59)(60)(61)(62)(63). Opposite to what we observed for PDCD5, depletion of PDCD2 in human acute leukemia cells impairs their proliferation, induces cell cycle arrest and p53 activation while overexpression of PDCD2 facilitates cell growth in cancers (55,64).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it was reported that PDCD5 also regulates autophagy to protect against cardiac remodeling (12). Dysregulation of PDCD5 has been found to be involved in different type of tumors (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The antitumor activity of PDCD5 has been also proposed (23)(24)(25)(26)(27)(28)(29) and low expression level of PDCD5 has been suggested to be a prognostic indicator for cancers (30).…”
Section: Introductionmentioning
confidence: 99%
“…11 The reduced expression of PDCD5 correlates with short survival periods of patients. 8,[12][13][14] Furthermore, it has been found that two single-nucleotide polymorphisms with linkage disequilibrium in the 5'-regulatory region of human PDCD5 gene reduce its promoter activity and increase susceptibility to chronic myeloid leukemia. 15,16 A single-nucleotide polymorphism in the 5'-upstream region of PDCD5 gene is predictive for lung cancer risk and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, PDCD5 expression decreases with increased tumor stage, reduced differentiation status, and metastasis to lymph nodes (2-7). Therefore, decreased PDCD5 gene expression is associated with poor prognosis of ovarian carcinoma, chondrosarcoma, and glioma (2,3,5). A combination of both in vitro and in vivo experiments confirmed that tumor cells expressing PDCD5 or treated with recombinant PDCD5 protein were more sensitive to chemotherapeutic drugs and UV irradiation.…”
Section: Introductionmentioning
confidence: 62%